T-type calcium channel blockade improves survival and cardiovascular function in thalassemic mice - Sirinart Kumfu (2018)
Objectives: Iron-overload cardiomyopathy is a major cause of morbidity and mortality in patients with thalassemia. However, the precise mechanisms of iron entry and sequestration in the heart are still unclear. Our previous study showed that Fe 2+ uptake in thalassemic cardiomyocytes are mainly mediated by T-type calcium channels (TTCC). Nevertheless, the role of TTCC as well as other transporters such as divalent metal transporter1 (DMT1) and L-type calcium channels (LTCC) as possible portals for iron entry into the heart in in vivo thalassemic mice under an iron-overload condition has not been investigated. Methods: An iron-overload condition was induced in genetically altered β-thalassemic mice and adult wild-type mice by feeding them with an iron diet (0.2% ferrocene w/w) for 3months. Then, blockers for LTCC (verapamil and nifedipine), TTCC (efonidipine), and DMT1 (ebselen) as well as iron chelator desferoxamine (DFO) were given for 1month with continuous iron feeding. Results: Treatment with LTCC, TTCC, DMT1 blockers, and DFO reduced cardiac iron deposit, cardiac malondialdehyde (MDA), plasma non-transferrin-bound iron, and improved heart rate variability and left ventricular (LV) function in thalassemic mice with iron overload. Only TTCC and DMT1 blockers and DFO reduced liver iron accumulation, liver MDA, plasma MDA, and decreased mortality rate in iron-overloaded thalassemic mice. Conclusions: DMT1, LTCC, and TTCC played important roles for iron entry in the thalassemic heart under an iron-overloaded condition. Unlike LTCC blocker, TTCC blocker provided all benefits including attenuating iron deposit in both the heart and liver, reduced oxidative stress, and decreased mortality in iron-overloaded mice. © 2012 John Wiley & Sons A/S.